Strategi Promosi UMKM Susu Kedelai Kota Bengkulu Perspektif Ekonomi Syariah - Yolanda, Agnes; Azis, Ismi; Oktasari, Orin; Yanto, Syafri; Capriyanti, Orisa (Politeknik Raflesia Press, 2023)
This research aims to find out how the promotional strategy for soybean milk MSMEs can be formulated at the Salafiyah Hidayatul Qomariyah Islamic Boarding School in Bengkulu City and what the promotional strategy for soybean milk MSMEs at the Salafiyah Hidayatul Qomariyah Islamic Boarding School in Bengkulu City is from a sharia economic perspective. as in this study the population was 12 people among MSME administrators and this study used a purposive sampling technique. Data was obtained using interview techniques. The research results of the strategy have gone well. Using 2 strategic systems, namely the traditional system by promoting directly to the students, guardians of the students and the surrounding community during visits and recitation days, both the 3rd Jum'ah recitation and other recitations. Then the second system uses a modern system, namely by using cellphone communication technology through various social media such as WhatsApp and Facebook. The Islamic view regarding promotional strategies is in accordance with the provisions of Islamic law, such as truth and honesty when promoting which is applied by the management, in terms of price. which is in accordance with the market price, which is in accordance with sharia pricing, then the syrup dosage has been adjusted to the size without reducing it. Shodaqoh and infaq are also distributed by the management to orphaned students and also to role model students and underprivileged students at the Hidayatul Qomariyah Islamic boarding school by reducing payments every month and some are even free until the students complete their education level. Keywords: Strategy, Promotion, UMKM